Trimeric Autotransporter Adhesins in Members of the Burkholderia Cepacia Complex: A Multifunctional Family of Proteins Implicated in Virulence - Fialho, Arsénio M.; Mil-Homens, Dalila (Frontiers in Cellular and Infection Microbiology, 2011)
Trimeric autotransporter adhesins (TAAs) are multimeric surface proteins exclusively found in bacteria. They are involved in various biological traits of pathogenic Gram-negative bacteria including adherence, biofilm formation, invasion, survival within eukaryotic cells, serum resistance, and cytotoxicity. TAAs have a modular architecture composed by a conserved membrane-anchored C-terminal domain and a variable number of stalk and head domains. In this study, a bioinformatic approach has been used to analyze the distribution and architecture of TAAs among Burkholderia cepacia complex (Bcc) genomes. Fifteen genomes were probed revealing a total of 74 encoding sequences. Compared with other bacterial species, the Bcc genomes contain a large number of TAAs (two genes to up to eight genes, such as in B. cenocepacia). Phylogenetic analysis showed that the TAAs grouped into at least eight distinct clusters. TAAs with serine-rich repeats are clearly well separated from others, thereby representing a different evolutionary lineage. Comparative gene mapping across Bcc genomes reveals that TAA genes are inserted within conserved synteny blocks. We further focused our analysis on the epidemic strain B. cenocepacia J2315 in which seven TAAs were annotated. Among these, three TAA-encoding genes (BCAM019, BCAM0223, and BCAM0224) are organized into a cluster and are candidates for multifunctional virulence factors. Here we review the current insights into the functional role of BCAM0224 as a model locus.